Structural biology of S-adenosylmethionine decarboxylase - Bale, Shridhar; Ealick, Steven E (Amino acids, 2010)
S-adenosylmethionine decarboxylase (AdoMetDC) is a critical enzyme in the polyamine biosynthetic pathway and a subject of many structural and biochemical investigations for anti-cancer and anti-parasitic therapy. The enzyme undergoes an internal serinolysis reaction as a post-translational modification to generate the active site pyruvoyl group for the decarboxylation process. The crystal structures of AdoMetDC from Homo sapiens, Solanum tuberosum, Thermotoga maritima, and Aquifex aeolicus have been determined. Numerous crystal structures of human AdoMetDC and mutants have provided insights into the mechanism of autoprocessing, putrescine activation, substrate specificity, and inhibitor design to the enzyme. The comparison of the human and potato enzyme with the T. maritima and A. aeolicus enzymes supports the hypothesis that the eukaryotic enzymes evolved by gene duplication and fusion. The residues implicated in processing and activity are structurally conserved in all forms of the enzyme, suggesting a divergent evolution of AdoMetDC.